ПЕРСПЕКТИВЫ ИССЛЕДОВАНИЯ ЭКСТРЕМОФИЛЬНЫХ МИКРООРГАНИЗМОВ В КАЗАХСТАНЕ (Experimental biology, 2017)
In this paper we studied the antagonistic properties of actinomycetesfrom saline soil in the Almaty region neutral saline and alkaline conditions of life of producers
Keywords: antagonistic properties; alkaline; producers